1999
DOI: 10.1090/s0025-5718-99-01164-3
|View full text |Cite
|
Sign up to set email alerts
|

An additive Schwarz method for variational inequalities

Abstract: Abstract. This paper proposes an additive Schwarz method for variational inequalities and their approximations by finite element methods. The Schwarz domain decomposition method is proved to converge with a geometric rate depending on the decomposition of the domain. The result is based on an abstract framework of convergence analysis established for general variational inequalities in Hilbert spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…The linear complementarity problem (5.2) can be solved by the projected SOR method [26], multilevel methods [38,57], domain decomposition methods [6], and interior point methods [8]; see [35] and references therein. We used the projected SOR method in our simulations.…”
Section: Implementation Detailsmentioning
confidence: 99%
“…The linear complementarity problem (5.2) can be solved by the projected SOR method [26], multilevel methods [38,57], domain decomposition methods [6], and interior point methods [8]; see [35] and references therein. We used the projected SOR method in our simulations.…”
Section: Implementation Detailsmentioning
confidence: 99%
“…. , π m ) may be viewed as the algorithmic mapping associated with the block Jacobi method for solving (1). Consider an asynchronous version of the block Jacobi method, parameterized by a stepsize γ ∈ (0, 1], which for simplicity we assume to be fixed, that generates a sequence of iterates (u 1 (t), .…”
Section: An Asynchronous Space Decomposition Methodsmentioning
confidence: 99%
“…. , K m are not all subspaces, there are various convergence studies for synchronous methods (see [1,12,23,25,28,29,30,31,34,35,36,47,50] and references therein) but, again, none for asynchronous methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Badea and Tai et al [15][16][17][18][19][20][21][22] have previously applied domain decomposition techniques to a constrained convex minimization problem coming from variational inequalities using space decomposition method. It has been shown that multigrid can be viewed as a special case of such space decomposition.…”
Section: 14mentioning
confidence: 99%